Efektivitas Eco Enzyme Sebagai Biokatalisator Proses Anaerob Untuk Mendegradasi Parameter TSS, Surfaktan, dan Fosfat - Honest Lazuardi; Yayok Suryo Purnomo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The pollution of rivers by domestic waste has become a serious problem affecting water quality. To address this problem, the use of ecoenzymes has been proposed as a solution for domestic waste treatment. In this study, different concentrations of ecoenzymes (10%, 20%, 25%) in the anaerobic process and retention time (2, 4, 6 days) were used to measure the degradation of organic parameters such as TSS (Total Suspended Solids), surfactants and phosphates. The results of the study indicate a significant reduction in TSS, surfactants and phosphates. The optimum concentration for TSS reduction was found to be 10%, while for surfactants and phosphates it was 25%. The optimum retention time for all parameters was found to be 6 days. These results provide an effective and economical solution for reducing river water pollution caused by domestic waste. It is hoped that the results of this study will provide another option for the treatment of domestic wastewater and the maintenance of river water quality.